m≠nのとき
1/{(2Wt-n)(2Wt-m)}={1/(m-n)}[{1/(2Wt-m)}-{1/(2Wt-n)}]
だから
∫_{-∞~∞}S_n(t)S_m(t)dt
=∫_{-∞~∞}sinπ(2Wt-n)sinπ(2Wt-m)/(π^2(2Wt-n)(2Wt-m))dt
=[1/{π(m-n)}]*
[∫_{-∞~∞}{sinπ(2Wt-n)sinπ(2Wt-m)}/{π(2Wt-m)}dt
-∫_{-∞~∞}{sinπ(2Wt-n)sinπ(2Wt-m)}/{π(2Wt-n)}dt
]
=[1/{π(m-n)}]*
[∫_{-∞~∞}([sin{x+(m-n)π}sinx]/x)dx
-∫_{-∞~∞}([sin{x+(n-m)π}sinx]/x)dx
]
=[1/{π(m-n)}]*
[∫_{-∞~∞}([sin{x+(m-n)π}sinx]/x)dx
-∫_{-∞~∞}([sin{x+(m-n)π}sinx]/x)dx
]
=0
m=nのとき
(d/dt)[(-1/2W)(2Wt-n)^{-1}]=(2Wt-n)^{-2}
だから部分積分すると,
∫_{-∞~∞}S_n(t)S_m(t)dt
=(1/π^2)∫_{-∞~∞}[{sinπ(2Wt-n)}^2/(2Wt-n)^2]dt
=(1/π^2)*
[(-1/2W){sinπ(2Wt-n)}^2(2Wt-n)^{-1}]_{-∞~∞}
+∫_{-∞~∞}[{2πsinπ(2Wt-n)cosπ(2Wt-n)}/(2Wt-n)]dt
]
=(1/π)∫_{-∞~∞}{[sin{2π(2Wt-n)}]/(2Wt-n)}dt
={1/(2πW)}∫_{-∞~∞}{[sinx]/x}dx
=1/(2W)